RETRACTED: Effects of Aidi injection on life quality and incidence of adverse reactions in patients with non-small cell lung cancer compared with traditional chemotherapy: a systematic review and meta-analysis - Fang, Qing; Yu, Biyun; Xu, Hui; Xu, Yuanyuan (Frontiers in Oncology, 2023)
Objective: To evaluate the effect of Aidi injection on life quality and incidence of adverse reactions in patients with non-small cell lung cancer (NSCLC) compared with traditional chemotherapy. Methods: PubMed, EMBASE, ScienceDirect, Cochrane Library, China Journal full-text Database (CNKI), VIP full-text Database, Wanfang Database and Chinese Biomedical Literature data (CBM), search relevant Chinese and foreign periodicals, conference papers, degree papers, etc.were searched Database and China Biomedical Literature Database (CBM) to search case-control trials of Aidi injection when treating NSCLC patients. The retrieval period begins with the establishment of the database and ends when the database is closed. Cochrane Handbook 5.3 was adopted to assess the bias risk of each contained literature based on independently extracted data by two researchers. A meta-analysis of the collected data was carried out using RevMan5.3 statistical software. Conclusion: Based on routine chemotherapy associated with Aidi injection, the therapeutic effect of NSCLC patients can be noticeably enhanced, the effective rate of treatment can be noticeably promoted, the immune function and life quality can be improved, and the incidence of adverse reactions is low, which is worth popularizing in clinical practice, but several studies and follow-ups are needed to improve methodological quality and to verify the results over a longer period of time.